A simple, robust and rapid approach to detect carbapenemases in Gram‐negative isolates by MALDI‐TOF mass spectrometry: validation with triple quadripole tandem mass spectrometry, microarray and PCR. (12th December 2014) - Vogne, C.; Prod'hom, G.; Jaton, K.; Decosterd, L. A.; Greub, G.; Cantón, R.
Abstract Carbapenemases should be accurately and rapidly detected, given their possible epidemiological spread and their impact on treatment options. Here, we developed a simple, easy and rapid matrix‐assisted laser desorption ionization‐time of flight (MALDI‐TOF)‐based assay to detect carbapenemases and compared this innovative test with four other diagnostic approaches on 47 clinical isolates. Tandem mass spectrometry (MS‐MS) was also used to determine accurately the amount of antibiotic present in the supernatant after 1 h of incubation and both MALDI‐TOF and MS‐MS approaches exhibited a 100% sensitivity and a 100% specificity. By comparison, molecular genetic techniques (Check‐MDR Carba PCR and Check‐MDR CT103 microarray) showed a 90.5% sensitivity and a 100% specificity, as two strains of Aeromonas were not detected because their chromosomal carbapenemase is not targeted by probes used in both kits. Altogether, this innovative MALDI‐TOF‐based approach that uses a stable 10‐μg disk of ertapenem was highly efficient in detecting carbapenemase, with a sensitivity higher than that of PCR and microarray.